REGISTER NELAYAN DI SUNGAI KAKAP KABUPATEN KUBU RAYA: KAJIAN SOSIOLINGUISTIK - Derry Kurniawan; Ahmad Muzammil; Agus Syahrani (Universitas Tanjungpura, 2020)
AbstractRegister is a variation of language that is caused due to the specific characteristics of the need for used or certain purposes as opposed to the dialect. The problem in this research are what types of register, the elements of the register, and what influence factors used of fisherman registers, supplement form description text material on the speech of fishermen in the Kakap River, Kubu Raya Regency, as Indonesian Language learning Curriculum 2013. The method used in this research is qualitative. The data source of this research is Pontianak Malay spoken by informants in Sungai Kakap, Kubu Raya Regency. Data collection techniques are tapping techniques, competent and free listening techniques, record and note techniques. Based on the conclusion, there are 25 registers used by fishermen. Closed register types as many as 9 registers and 16 open registers. The register element used is a discourse field of 14 registers, a discourse facility of 1 register, and the first discourse involved as many as 13 registers and a second discourse involved as many as 12 registers. There are 8 factors that influence the use of registers, namely, setting, participant, ends, act, key, instrumentalities, norms, and genre. This research has a relation to Curriculum 2013 in Indonesia Language Subjects in the seventh grade of students on semester of junior high school, and the researcher suggested to be a learning implementation plan (RPP) for teaching and learning activities in schools.Keywords: Fishermen in the Kakap River, Speech Events, Register.